ROZKŁAD OPADÓW ATMOSFERYCZNYCH W OKOLICY ZIELONEJ GÓRY W LATACH 1991–2014 - KLEINERT, KATARZYNA (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2020)
This thesis aims at characterising the distribution of precipitation in the region of Zielona Góra in 1991–2014. An attempt was made to explain the influence of landform and forest cover on precipitation. In the area of interest, summer rainfall prevails with more frequent but less abundant winter precipitation. The highest precipitation has been observed on the western slopes of Zielona Góra Ridge and by the Lower Bóbr River Valley, whereas Zbąszyń, located further to the north-east, is the driest station.